2022
DOI: 10.21831/jpe.v10i1.40504
|View full text |Cite
|
Sign up to set email alerts
|

The development of multicultural education comics to embed tolerance character for 4th grade of elementary school

Abstract: This research aims to produce a comic book that can be used to embed the character of tolerance to the students of 4th grade of elementary school. This research using development procedure from Borg and Gall includes seven steps procedure, they are research and information collecting, planning, developing a preliminary form of product, preliminary field testing, main product revision, main field testing, and operational product revision. The data resources were collected from interviews, observation, and quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…For this reason, through multicultural education as a forum to instill awareness of multicultural values and awareness that the diversity of life is a reality that must be faced and addressed with wisdom, of course, planting a concept like this is done without reducing the purity of each religion that is believed to be true by students. This must be confirmed so that there is no misunderstanding (Anggito & Sartono, 2022;Aslan & Aybek, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…For this reason, through multicultural education as a forum to instill awareness of multicultural values and awareness that the diversity of life is a reality that must be faced and addressed with wisdom, of course, planting a concept like this is done without reducing the purity of each religion that is believed to be true by students. This must be confirmed so that there is no misunderstanding (Anggito & Sartono, 2022;Aslan & Aybek, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…The whiteboard animation proclamation-based is prepared to attract students' interest to enhance the patriotism of fourth-grade elementary students. Media layouts are well designed, illustrated and well laid out, and adapted for elementary school students (Anggito & Sartono, 2022). The whiteboard animation proclamation-based that was developed contains a choice of words, language, and color combinations, which are adapted to the characteristics of students (Sabrin, Soeharto, & Kurniadi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This can be used as a variation in the form of comics which are still dominant in hardfiles. As research by (Anggito & Sartono, 2022;Handayani & Koeswanti, 2020;Soeharto, 2015) can be concluded that comics can be used as learning media that are useful for various important purposes in education…”
Section: ) Mann Whitney Difference Testmentioning
confidence: 99%
“…The difference in this study is that the comics used are still paper-based comics, while the comics developed by the researchers have integrated augmented reality technology. Another relevant research by Anggito & Sartono (2022) shows that comics media are feasible to be used in improving social studies learning achievement and students' tolerance character. The difference with the research conducted is in the dependent variable studied and the comic media that has not integrated augmented reality technology.…”
Section: Figure 1 Diagram Of Students' Daily Reading Intensitymentioning
confidence: 99%